Kalimat Imperatif Dalam Kitab “Itsbȃt Ramaḍȃn” Karya Ali Mustafa Yaqub: Kajian Semantik - Ramadhani, Hekmatiar; Fahmi, Kaula; Suparno, Darsita; Nisa’, Mauidlotun; Mubarak, M. Zacky; Attih, Idriss (EL-FUSHA: Jurnal Bahasa Arab dan Pendidikan, 2025)
This study aims to describe the forms and meanings of imperative sentences found in Itsbât Ramaḍân wa Syawwâl wa Dzu al-Ḥijjah ‘alâ Ḍaw’ al-Kitâb wa al-Sunnah by Ali Mustafa Yaqub from a semantic perspective. This research employs a descriptive qualitative method. The data collection method applied in this study is documentation, using reading and note-taking techniques. The data analysis technique employs a taxonomic approach, consisting of data organization and meaning interpretation stages. The results of the study indicate that: (1) There are 30 imperative sentences in Itsbât Ramaḍân wa Syawwâl wa Dzu al-Ḥijjah ‘alâ Ḍaw’ al-Kitâb wa al-Sunnah, comprising 28 sentences in the form of fi‘il al-amr and 2 sentences in the form of ism fi‘il al-amr; and (2) The types of meanings of the imperative sentences are divided into five categories, namely 12 sentences with the meaning of genuine command (amr ḥaqīqī), 5 sentences meaning supplication (al-du‘ā), 1 sentence expressing choice (al-takhyīr), and 5 sentences implying threat (al-tahdīd).